2009
DOI: 10.1163/156856809789822998
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distance between target and irrelevant patch modulates detection in a texture segmentation task

Abstract: Abstract-In three texture segmentation experiments a target patch had to be detected. We studied the impact of a task-irrelevant patch in the backward mask on detection performance, and especially the modulating effects of its spatial distance to the target. It was assumed that the signals of the two texture irregularities interact as a function of their spatial distance. Experiment 1 revealed that the taskirrelevant patch impaired target detection only when the distance was small. In Experiments 2 and 3 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…The distance-dependency of the patch-effect in our study is similar to that reported by Schade and Meinecke (2009, 2011), however, they studied iso -dimensional texture irregularities (orientation). Cross-dimensional distance effects and critical distances were observed in visual search tasks, as mentioned in the Introduction Section.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The distance-dependency of the patch-effect in our study is similar to that reported by Schade and Meinecke (2009, 2011), however, they studied iso -dimensional texture irregularities (orientation). Cross-dimensional distance effects and critical distances were observed in visual search tasks, as mentioned in the Introduction Section.…”
Section: Discussionsupporting
confidence: 89%
“…There is already experimental evidence for spatial signal competition on feature map level from two texture segmentation studies (Schade and Meinecke, 2009, 2011). In those studies, a texture irregularity in the stimulus was the target to be detected, and a task-irrelevant texture irregularity (“patch”) was inserted into the backward mask; the spatial distance between target and patch was varied systematically.…”
Section: Introductionmentioning
confidence: 99%